1989
DOI: 10.1115/1.3259021
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Balancing of the Stiller-Smith Mechanism for Application to an Eight-Cylinder IC Engine

Abstract: The Stiller-Smith Mechanism employs a double cross-slider to convert linear reciprocating motion into rotational motion. It has previously been shown that a four-cylinder configuration utilizing this motion conversion device can be balanced in two dimensions. The inherent planar nature of this mechanism makes it possible to produce a compact, eight-cylinder configuration for use as an internal combustion engine which is balanced in three dimensions. This paper develops and presents the necessary requirements f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Connecting rod Piston Output shaft Counterweights (if needed)* * It has been shown that some configuratlons do not requlre counterweights (25) Bearing supports Housing Each of these subroutines also yields the weight of each of the components which are then added up to yield their contribution to the total engine weight.…”
Section: Other Component Subroutinesmentioning
confidence: 99%
“…Connecting rod Piston Output shaft Counterweights (if needed)* * It has been shown that some configuratlons do not requlre counterweights (25) Bearing supports Housing Each of these subroutines also yields the weight of each of the components which are then added up to yield their contribution to the total engine weight.…”
Section: Other Component Subroutinesmentioning
confidence: 99%